Morbidity Profile in Under Five Children in Urban Slum Area of Nagpur - Vinod Narkhede; Umesh Sinha; Sumit D Bhardwaj; Smita Pitale (Medsci Publications, 2012)
Introduction: Childhood diseases like diarrhoea, respiratory infections, measles, etc are very common in India. It is known that a child may get affected several times in a year; the incidence increases with the aggravation of a state of malnutrition. Aim: The study was aimed to assess the malnutrition and morbidity profile in underfive children in urban slum area of Nagpur. Material & Methods: A house-to-house survey was conducted. By systematic random sampling 434 children below five years of age were included in the study. Every attempt was made to cover maximum number of children by giving 3 visits to them. Total 404 children were covered in the study. The information obtained from child's mother was filled in the proforma. Every child was subjected to thorough clinical examination in daylight, and anthropometric measurements. Hemoglobin estimation was done by using Sahli's haemoglobinometer and peripheral smear was prepared. Data was analyzed on Epi-Info Software 3.2 version. Chi square test is used to test the significance. Result: It was observed that highest prevalence of morbidity was of anaemia (78.71 percent), most of them were nutritional: followed by protein energy malnutrition (IAP classification) was 52.23 percent, vitamin B deficiency (46.53 percent), disease of respiratory system 32.19 percent). Conclusion: More than three-quarter of children from urban slum were suffering from anaemia and had high burden of under nutrition. Large proportion of morbidities in the under 5 children could be attributed to the nutritional status.